Prevalence of intermittent exotropia among primary and secondary school students in Shantou, China - LinShibin; GongWeifen; ChenBin; ZhangMingzhi (眼科学报; 卷 31, 编号 1 (March 2016): 《眼科学报》, 2016)
Background: Few prevalence studies on intermittent exotropia (IXT) based on Chinese populations. Furthermore, longitudinal change in this pattern within a local setting has not been reported in the past. This study aims to determine the profile of children with IXT in China. Methods: A total of 7,537 subjects from nine multi-layer primary and secondary schools participated in this investigation. The position of eyes was examined by using Hirschberg test and alternate cover test. The obtained results were classified according to respective features and analyzed statistically. Results: The prevalence of IXT among the participants was 7.98%, accounting for 73.04% of all types of strabismus. Junior high school students had a lower prevalence of IXT than elementary and senior high school counterparts. Logistic regression analysis showed that IXT was mainly found in male pupils at high grades in rural areas and in male secondary students at high grade in urban regions. Conclusions: IXT was shown to be more prevalent than other types of strabismus in Chinese children. Furthermore, the distribution and characteristics of IXT greatly varied among participants.